Advanced Differentiated Thyroid Cancer: A Complex Condition Needing a Tailored Approach - Bulfamante, Antonio Mario; Lori, Eleonora; Bellini, Maria Irene; Bolis, Elisa; Lozza, Paolo; Castellani, Luca; Saibene, Alberto Maria; Pipolo, Carlotta; Fuccillo, Emanuela; Rosso, Cecilia; Felisati, Giovanni; De Pasquale, Loredana (Frontiers in Oncology, 2022)
Differentiated thyroid cancers (DTCs) are slow-growing malignant tumours, including papillary and follicular carcinoma. Overall, prognosis is good, although it tends to worsen when local invasion occurs with bulky cervical nodes, or in case of distant metastases. Surgery represents the main treatment for DTCs. However, radical excision is challenging, and significant morbidity and functional loss can follow the treatment of the more advanced forms. Literature on advanced thyroid tumours, both differentiated and undifferentiated, does not provide clear specific guidelines, and it emerges the need for tailored and multidisciplinary approach. In the present study, we report our single-centre experience of 111 advanced (local, regional and distant) DTCs, investigating the rate of radical excision, peri-procedural and post-procedural complications, quality of life, persistence, recurrence rates and survival. Results are critically appraised and compared to the existing published evidence review.